Analisis Perbandingan Classycal Probability dengan Metode Certainty Factor Dalam Penyelesaian Kasus Ketidakpastian (Studi Kasus : Identifikasi Jenis Racun Bisa Ular) - Ibnu Rusydi; Puji Sari Ramadhan (ALGORITMA : JURNAL ILMU KOMPUTER DAN INFORMATIKA, 2019)
Development of expert systems have been penetrated in the medical’s world, including amongothers is used to measure the level of certainty and probability in diagnosing symptoms thathappen to get an information about the illness, but to be able to know the methods that can havea high degree of accuracy the best results needs to be done the analysis comparison method,especially compared Classycal Probability method of Certainty Factor, in a comparison of thismethod refers to the case of identifying the type of poison venom in patients exposed to toxicvenom, so that this application can help the medical personnel and the public in doing thediagnosing to generate information quickly and accurately in order to do further treatment.Keywords: Expert System, Classical Probability, Certainty Factor, Type Snake Venom